Astrocyte–microglia crosstalk in subarachnoid hemorrhage: mechanisms and treatments - Kaibo Yu; Ding Wang; Wenhua Yu (Frontiers in Immunology)
Subarachnoid hemorrhage (SAH) is a frequently encountered critical emergency characterized by the rupturing of an unhealthy blood vessel, resulting in high mortality and disability rates. Alterations in the neurovascular unit (NVU) are closely related to the pathogenesis of SAH. Microglia, the primary innate immune cells in the brain, and astrocytes, the most abundant cells in the brain, both play crucial roles in the response to SAH-associated cerebral injuries. Recently, the crosstalk between these two cells in the pathology and treatment of central nervous system (CNS) diseases, including SAH, has been revealed. Following acute brain insult, activated microglia and astrocytes can further activate each other, contributing to amplified neuroinflammatory reactions and thus inducing secondary brain injury. This review addresses the pathophysiological mechanisms of microglia and astrocytes in SAH, including neuroinflammation, neuronal damage, blood–brain barrier (BBB) disruption, vasospasm, and hematoma clearance. In addition, the newly identified therapeutic strategies against SAH by regulating astrocytes-microglia crosstalk through targeting damage-associated molecular patterns (DAMPs), immune mediators, and their receptors are also discussed. A thorough comprehension of microglia–astrocyte communication could provide novel ideas for future research and treatment of SAH.